2020
DOI: 10.1186/s12934-020-01308-1
|View full text |Cite
|
Sign up to set email alerts
|

A probiotic treatment increases the immune response induced by the nasal delivery of spore-adsorbed TTFC

Abstract: Background: Spore-forming bacteria of the Bacillus genus are widely used probiotics known to exert their beneficial effects also through the stimulation of the host immune response. The oral delivery of B. toyonensis spores has been shown to improve the immune response to a parenterally administered viral antigen in mice, suggesting that probiotics may increase the efficiency of systemic vaccines. We used the C fragment of the tetanus toxin (TTFC) as a model antigen to evaluate whether a treatment with B. toyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Also, Santos et al reported the same results in which B. toyonensis probiotic bacterium increased IFN-γ cytokine in the vaccine system [32]. Our results are in line with the results of other studies.…”
Section: Discussionsupporting
confidence: 93%
“…Also, Santos et al reported the same results in which B. toyonensis probiotic bacterium increased IFN-γ cytokine in the vaccine system [32]. Our results are in line with the results of other studies.…”
Section: Discussionsupporting
confidence: 93%
“…Actually, Alloprevotella has been regarded as the cancer-related bacteria in colon cancer or visceral leishmaniasis (30,31). Moreover, a previous study showed that the abundance of the Ruminiclostridium genus was related to the enhancement of animal immune responses to spore adsorbent antigen and probiotics (32). Similarly, Prevotellaceae_UCG_001 was overrepresented in AOM/DSS mice in comparison to controls (33).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is known that recombinant spores of B. subtilis administered by gavage germinate in the stomach and small intestine and due to low oxygen present in the large bowel environment they re-sporulate displaying the heterologous antigen again [ 48 , 49 , 50 ] therefore, the oral delivery of recombinant B. subtilis spores would be also considered and interesting option since it allows higher doses and number of immunizations. Additionally, the use of adjuvants with immunostimulatory capacities, such as Toll-Like Receptors (TLR) and NOD-Like Receptor (NLR) ligands [ 51 ] or probiotics [ 52 ] might boost the expected immune response. A recent study has shown that humoral and cellular immune responses observed in mice nasally immunized with B. subtilis spores displaying the C fragment of the tetanus toxin (TTFC) on the surface were enhanced in mice previously submitted to Bacillus toyonencis as probiotic [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of adjuvants with immunostimulatory capacities, such as Toll-Like Receptors (TLR) and NOD-Like Receptor (NLR) ligands [ 51 ] or probiotics [ 52 ] might boost the expected immune response. A recent study has shown that humoral and cellular immune responses observed in mice nasally immunized with B. subtilis spores displaying the C fragment of the tetanus toxin (TTFC) on the surface were enhanced in mice previously submitted to Bacillus toyonencis as probiotic [ 52 ]. Therefore, the use of these kinds of strategies would contribute to an improvement in this work.…”
Section: Discussionmentioning
confidence: 99%